Pengaruh Tehnik Kombinasi Relaksasi Progresif Dan Relaksasi Otogenik Terhadap Kadar Gula Darah Pada Pasien Diabetes Melitus Tipe 2 Di Ruang Rawat Inap RSIJ Pondok Kopi - Revie Fitria Nasution; Restu Iriani (STIKes Persada Husada Indonesia, 2014)
Diabetes mellitus is a heterogeneous group of disorders characterized by an increase in glucose levels in the blood or hyperglycemia . This research was a quantitative study that used a quasi-experimental design, namely a study which provide a treatment or intervention studies on the subject . Treatment or intervention that is stated in this study is to provide progressive relaxation techniques and progressive relaxation combined action and autogenic . The goal of this research was to realized the effect of the value of blood sugar levels between the treatment of progressive relaxation techniques with the value of the blood sugar levels of progressive relaxation techniques combined with Autogenic relaxation. The locations used for this study was the RSIJ Pondok Kopi . The number of respondents used in this study was 15 respondents which are Type 2 diabetes patients who are undergoing hospitalization in Pondok Kopi RSIJ. The statistical test used was the Mean Two Different Test ( Paired Sample T - Test ). The results of this study found that the effect obtained on blood sugar levels from progressive relaxation techniques with a value of t = -4.56 ( p < 0.05 ) and progressive relaxation techniques and autogenic combination with the value t = -2.79 ( p < 0.05 ) . In conclusion of this study, the progressive relaxation techniques combined with superior autogenic relaxation techniques can assist in decreasing the blood sugar levels. Combination of progressive relaxation techniques and autogenic is recommended as part of an alternative independent nursing interventions in providing nursing care to patients with type 2 diabetes .